Membangun Wawasan Kebangsaan Melalui Media Podcast “Telinga Zaki” Bagi Generasi Muda Sebagai Agen Perubahan - Khodijah Khodijah; Zaki Ferdiansah; Jelita Nur Azizah; Naila Siti Wulandari; Maulia Depriya Kembara (Institut Nalanda, 2024)
In a time of increasingly complex globalization, maintaining national identity and patriotism is a significant challenge. The younger generation is the future successor and has the potential to shape the direction and identity of the nation. Technology has great potential to strengthen the sense of patriotism through various means such as means-based education, technology-based education, social media, and positive content that promotes national values. Collaboration between the government, private sector, and universities is important in building nationalistic insights in the younger generation. By utilizing technology and through good collaboration, the younger generation can become a force that drives nation-building and strengthens patriotism. This research uses a qualitative method that is taken based on the community's response to the video made. The results will be used as a measuring tool regarding the effect of building national insight through social media. The results illustrate that some people find the introduction of nationalistic insight through videos interesting. This is illustrated by the audience's appreciation and perceived usefulness. Through video podcasts that are currently developing, it will greatly facilitate the understanding of national insight by the younger generation. From this, the introduction of national insight is not always through formal things, but can be done through something non-formal.